Gerald's Emotional State in The Last Wish - Agustiana, Vina; Rahmatunisa, Wulan; Nuruliya, Shifa (Universitas Pendidikan Indonesia, 2023)
Psychology is a general concept that every human being possesses. Using Freud's Psychoanalytic Theory, this study investigates the types of Psychological Aspects found in Geralt, the main character in Andrzej Sapkowski's novel